Conversion of cysteine to formylglycine: A protein modification in the endoplasmic reticulum - Dierks, Thomas (The National Academy of Sciences of the USA, 1997)
In sulfatases a C(α)-formylglycine residue is found at a position where their cDNA sequences predict a cysteine residue. In multiple sulfatase deficiency, an inherited lysosomal storage disorder, catalytically inactive sulfatases are synthesized which retain the cysteine residue, indicating that the C(α)-formylglycine residue is required for sulfatase activity. Using in vitro translation in the absence or presence of transport competent microsomes we found that newly synthesized sulfatase polypeptides carry a cysteine residue and that the oxidation of its thiol group to an aldehyde is catalyzed in the endoplasmic reticulum. A linear sequence of 16 residues surrounding the Cys-69 in arylsulfatase A is sufficient to direct the oxidation. This novel protein modification occurs after or at a late stage of cotranslational protein translocation into the endoplasmic reticulum when the polypeptide is not yet folded to its native structure.